MEMBENTUK HUKUM YANG BERMORAL DAN BERADAB (MEMAKNAI KEMBALI IDEOLOGI PANCASILA DALAM PERSPEKTIF HUKUM ISLAM) - Hasib, Mohammad (IAIN Tulungagung, 2017)
Laws that are legitimized by the government are inclined to the year golden moral uncivilized law. Rather than aimed at authenticity and certainty in society, are laws made precisely only to protect the capitalist capitalists and the government of colle. Communities are often harmed by their constitutional rights owed to law enacted by the government. This can be seen from the banykanya accommodate of judicial review in the Constitu-tional Short which was decided with the verdict of granting either partially golden entirely. In fact, civilized and morale are always made by laws has morale institution have well. Yew in fact many laws reduce the rights of the celebrity, then it can be said that in law-makers actually doh not gaunt good morale to make the law. Pancasila have has lead star (leistar) has actually provided guidance to form has participatory and aspirational morale law through tea mechanism of deliberative democracy, tea law is called morally yew it empties and is based one tea ideology of Pancasila. Therefore it is necessary to re-actualize, reenforce and revitalize tea ideology of Pancasila by lawmakers and for law-making institutions to produce morale law, so that tea established law can create social justice for all Indonesian celebrity.Keyword: Pancasila Law, Social Justice, Islamic Law